Book Reviews - Oakes , Kathleen; O’Shea , Greg; French , Robert; Reed , Barbara; Moore , Peter (Archives & Manuscripts, 1985)
Future trends: proceedings of the 4th Biennial Conference reviewed by Kathleen Oakes p. 57-61; David B. Gracy. The small archive and reviewed by Greg O’Shea p. 61-63; J.A. Fraser and H.A. Averill. Organising an archives … reviewed by Robert French p. 63-64; Guide to the records relating to science and technology in the British Public Recors Office and Guide to manuscripts relating to science in the Alexander Turnbull Library reviewed by Barbara Reed p. 65-67; Patrick O’Farrell. Letters from Irish Australia reviewed by Peter Moore p. 67-69